1998
DOI: 10.1111/j.1600-0609.1998.tb01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparable TNF‐alpha, IFN‐gamma and GM–CSF production by purified normal marrow CD3 cells in response to horse anti‐lymphocyte and rabbit antithymocyte globulin

Abstract: In vitro priming of T cell with horse antilymphocyte globulin (HALG) results in cytokine release, and this has been associated with its clinical efficacy in patients with severe aplastic anaemia (SAA). Rabbit antithymocyte globulin (RATG) has been studied less extensively. In this study we compare the in vitro priming effect of HALG and RATG on purified normal marrow T cells: end‐points of the study were 1) levels of TNF‐alpha (TNF‐α), IFN‐gamma (IFN‐γ) GM–CSF in T cell supernatants, and 2) effect of T cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several cytokines are released as a result of cell lysis. In vitro experiments demonstrated that ATG induces CD3 + or CD4 + T cells and natural killer cells to produce several cytokines such as IFN‐γ, tumor necrosis factor (TNF)α, interleukin (IL)‐2, IL‐4, IL‐6, IL‐10, and granulocyte macrophage colony‐stimulating factor . Among these, IFN‐γ, TNFα, IL‐2, and IL‐6 are known endogenous pyrogens .…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines are released as a result of cell lysis. In vitro experiments demonstrated that ATG induces CD3 + or CD4 + T cells and natural killer cells to produce several cytokines such as IFN‐γ, tumor necrosis factor (TNF)α, interleukin (IL)‐2, IL‐4, IL‐6, IL‐10, and granulocyte macrophage colony‐stimulating factor . Among these, IFN‐γ, TNFα, IL‐2, and IL‐6 are known endogenous pyrogens .…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that we could not yet identify additional factors contributing to the impaired clonogenic potential of HSPC after ATGt. TNF or interleukin‐6 might be relevant players because they are also increased after ATGt 9,23 . Moreover, TNF is known to contribute to BM failure in AA 32 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Despite being beneficial for the depletion of autoreactive T cells, 8 ATG administration also results in a massive release of inflammatory cytokines such as IFN-γ, tumor necrosis factor (TNF), and other interleukins. 9,10 Eltrombopag (EPAG) induces downstream signaling of the TPO-R 11 and was recently introduced in the therapy of refractory AA due to its ability to improve hematopoiesis as monotherapy and in combination with IST. [12][13][14] A recent study has shown that EPAG enhances HSPC function by bypassing the IFN-γ-mediated perturbation of the TPO axis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations